Earth, fire and air essays of a decade - Mayuga, Sylvia L. (Manila Anvil Publishing House, 1992)
Shortly before the Aquino assassination, the Manila Daily Bulletin’s “four horsewomen of the Apocalypse” were fired in succession. As Philippine history took a dramatic turn, Sylvia L. Mayuga, Arlene Babst, Niñez C. Olivares, and Melinda Q. de Jesus found themselves at the forefront of a struggle for the full restoration of press freedom. Earth, Fire, and Air records the changing of the guards and the events soon after, with the passion of an activist and the sensitivity of a poet.
I. RESTLESS BEFORE A STORM: I Remember Satur -- A Tale of Four Writers -- Free the Artist! -- Reflections on Objectivity -- Anatomy of a Birth Announcement.

II. CHANGING OF THE GUARDS: Moment of Truth -- Just Another Human Being -- Flash Forward -- The View from the Flagpole -- The Strangest Rally -- A Banker's Tale -- Lessons from Bayan -- Looking for Bayan -- Mommy vs. Daddy -- No Illusions.

III. WAR AND PEACE: Cannibals and Christians -- Life and Death in a War Zone -- Disbelief at the Manila Hotel -- Can the Center Hold -- A Balinese Umbrella -- Graduating from Labels -- A Vibration of the Heart -- The Sunflowers are Weeping -- Full Circle With the Revolution -- Circle on the Square.

IV. HEROES AND VICTIMS: The Sampaguita Vendor and Co. -- Dear Tetchie -- To be a Priest -- A Godless Dissident -- Pearly Shell -- In Love with a Communist -- Down to Earth -- An Antidote to His Time -- The General and Demo-crazy -- A Writer's Passing -- To Our Graduate.

V. CHAFF FROM GRAIN: A Rose in the Snow -- Dogfight on Dog Year -- Closing the Gap -- You May Go Now, Maharishi -- Much Ado About an MTV -- Mother's Kids -- My Friend, the Duende -- The Real Thing -- My Mother's Garden -- Once in a Blue Moon.

VI. MOTHER EARTH: Mary, Ancient Mother -- Green Dialogues -- A Mountain-climbing lawyer -- How to Clean a River -- The Long Road to Wizardy -- A Radioactive Heart -- And Now, the Artquake -- Tale of an Aeta Exodus.

VII. GOLD OF THE ANCIENTS: People Sprung from the Earth -- Centering the Grain -- Gold of the Ancients -- Festival of Revelation.

VIIII. A PILGRIM'S PROGRESS: A Blessing by the Sea -- Among the Peasant Hills -- Beauty and the Beast -- A Summer for the Faith -- Life and Death in the U.S.S.R. -- That Autumn in Germany -- The Music of Jericho -- Vaclav Havel, Philosopher President.
Keywords: Philippine essays (English)